The Effect of Toothpaste with Nanocalcium and Nanochitosan on Oral Cavity Microorganism (in vivo) - Octarina Octarina; Stieven Rey; Komariah Komariah (Jurnal Material Kedokteran Gigi, 2018)
Mangrove crab shell and horn beetle can be modified into nanocalcium and nanochitosan. Nanocalcium has an effect to remineralize the tooth surface, while the nanochitosan act as an antibacterial. The purpose of this study was to determine the number of microorganism after brushing with toothpaste which containing nanocalsium and nanochitosan. In this study, toothpaste was made with nanocalsium and nanochitosan with three formulations i.e. 25% nanocalsium + 3gr nanochitosan, 55% nanocalsium + 3gr nanochitosan, and 75% nanocalsium + 3gr nanochitosan. The sample of toothpaste is tested on 25 primary school children (8-9 years old) and divided into five treatments: 25% nanocalsium + 3gr nanochitosan (K1), 55% nanocalsium + 3gr nanochitosan (K2), and 75% nanocalsium + 3gr nanochitosan (K3), commercial toothpaste (K4), and without toothpaste (K5). The result of gargling was taken before and after tooth brushing. This study used TPC test with diffusion method that embedded in sodium agar which counting the decrease of oral microorganism. The data is processed using repeated ANOVA. The result of counting microorganism for five treatments before tooth brushing respectively were K1 = 1610.4±1380.59, K2 = 979±675.46, K3 = 1275.8±809.99, K4 = 550±840.37, K5 = 1086.8±840.37 and after the treatments were K1 = 142±191.36, K2 = 102.8±118.55, K3 = 161.4±122.26, K4 = 197±210.64, K5 = 88.8±20.66 (p< 0.05). The conclusion, there is a decrease of microorganism in the oral cavity after tooth brushing. The toothpaste that containing nanocalcium and nanochitosan shows more effectively to inhibit microorganism in oral cavity than commercial toothpaste.